Pengaruh Temperatur Aktivasi Karbon Aktif Terhadap Adsorpsi Logam Besi (Fe) Pada Limbah Batik Cair Batik Cual - Pornawati, Heni; Aldila, Herman; Kurniawan, Widodo Budi (Jurusan Fisika, Universitas Bangka Belitung, 2024)
Batik cual waste is a problem that is quite dangerous if it is disposed of directly into the environment because it contains various kinds of heavy metals such as iron Fe. To overcome the problem by utilizing coconut shell as activated carbon. In this study, the activated carbon used was the result of chemical activation and physical activation processes using temperatures of , and . Based on the SEM results to determine the sphericity value for a temperature of is worth 0.47 for is worth 0.56 and for is worth 0.52. The value of the pore diameter of activated carbon at temperatures of , and is 40.11µm, 81.84µm and 55.50µm. The BET results for activated carbon have a total pore volume for temperatures of , and with values of 0.182 cc/g, 0.2315 cc/g and 0.1605 cc/g. To decadarize cual batik wastewater through the adsorption process, temperatures of , and were used with contact times of 0, 40, 80, 120 and 160 minutes. The adsorption results were carried out by kinetic modeling using first-order, second-order and BMG kinetic models. Based on the model that is most suitable for the adsorption of liquid batik wastewater is BMG